Origen the Sophist: Anti-Sophistic Polemic in Porphyry's "Contra Christianos" - Becker, Matthias (Vigiliae Christianae, 2019)
Making use of Beatrice Wyss' "pattern of the disparagement of sophists" for heuristic purposes, this paper argues that the depictions of Christian exegetes and scholars in a fragment of Porphyry's lost work Contra Christianos (fr. 39 Harnack/fr. 6F. Becker) contain literary elements of ad hominem attacks which were used in Greek anti-sophistic polemic. Porphyry's allusive language allows for the conclusion that he aimed specifically at casting Origen in the role of a sophist. This hitherto unnoticed component of Porphyry's polemic against the Christians sheds light on how Platonists in the third century viewed Christian intellectuals through a Platonic lens in order to secure their identity against a stereotypical opponent which had ultimately been created by Plato himself. Thus, in Porphyry's view, Christians are, as it were, new foes with old familiar faces.